Mengatur Media Ramah Anak: Peran Konsumsi Media untuk Anak di Indonesia - Nurhaqiqi, Hanna; Rachmawati, Farikha (Universitas Djuanda Bogor, 2025)
The media industry in Indonesia is experiencing rapid growth, along with an increasing number of audiences from various groups, including children and parents. Children, as part of the audience, have different characteristics from other age groups. Providing child-friendly media is crucial. This study aims to examine the perceptions and views of media activists and parents regarding the existence and quality of child-friendly media in Indonesia. The method used in this study was a qualitative approach with in-depth interviews with eight respondents, consisting of four media activists and four parents. Data analysis was conducted using the perspective of George Gerbner's Uses and Gratification Theory, as well as the Media Regulation theory of Sonia Livingstone and Peter Lunt. The results show that both media activists and parents believe that child-friendly media in Indonesia is currently still not optimal in meeting children's needs and interests. Available content is considered limited, less relevant to current developments, and does not fully support educational aspects or healthy entertainment for children. These findings emphasize the importance of collaboration between the media, government, and society to create stricter regulations and encourage the production of higher-quality content that is appropriate to the needs of children in today's digital era.